2011
DOI: 10.12934/jkpmhn.2011.20.4.404
|View full text |Cite
|
Sign up to set email alerts
|

Critical Thinking Disposition and Self-esteem of Psychiatric Mental Health Nurses

Abstract: Purpose:The purpose of this study was to identify the critical thinking disposition and self-esteem of psychiatric nurses and to identify factors that influence critical thinking disposition. Methods: A cross-sectional study design was used in this study. The participants for this study were 158 psychiatric nurses from D city & C province. The instruments were the California Critical Thinking Disposition Inventory (CCTDI) and Self-Esteem Scale (SES). The collected data were analyzed using t-test, ANOVA, Pearso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Additionally, the production of highly qualified professionals is one of the prerequisites for the implementation of such national health-related policies. The change in societal attitude towards mental health issues has led to an increase in expectations and the duties for mental health nurses [1]. Consequently, demand for quality mental health care has become a new stressor for nurses.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the production of highly qualified professionals is one of the prerequisites for the implementation of such national health-related policies. The change in societal attitude towards mental health issues has led to an increase in expectations and the duties for mental health nurses [1]. Consequently, demand for quality mental health care has become a new stressor for nurses.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that nurses' self-esteem is significantly and positively related to critical thinking. 32 Improving nurses' self-esteem is helpful in improving their critical thinking. 33 When nursing managers pay attention to improving the level of self-esteem of nurses, they should also focus on cultivating nurses' critical thinking skills to improve the level of clinical decision-making.…”
Section: Self-esteem Is Positively Correlated With Critical Thinkingmentioning
confidence: 99%